#### Answer

TRUE

#### Work Step by Step

$\lim\limits_{n \to \infty}(a_{n+3}-a_{n})=\lim\limits_{n \to \infty}a_{n+3}-\lim\limits_{n \to \infty}a_{n}$
Therefore,
$\lim\limits_{n \to \infty}(a_{n+3}-a_{n})=2-2=0$
Hence, the statement is true.

Published by
Cengage

ISBN 10:
1285740629

ISBN 13:
978-1-28574-062-1

TRUE

You can help us out by revising, improving and updating this answer.

Update this answerAfter you claim an answer you’ll have **24 hours** to send in a draft. An editor
will review the submission and either publish your submission or provide feedback.